DIAGNOSA AWAL PENYAKIT IBU HAMIL DENGAN PENDEKATAN CERTAINTY FACTOR - Eka Samuel P. Hutasoit; Darwis Robinson Manalu (Majalah Ilmiah METHODA, 2018)
Lack of knowledge about the early diagnosis of disease in pregnant women is very risky and can cause death. So it is very necessary to do socialization early to anticipate this. Based on the results of existing surveys if the handling is late, the mortality rate of pregnant women can increase. Then the use of technology and applications to help users (pregnant women) in making diagnoses before meeting with experts to help in knowing and detecting symptoms experienced. To produce the right solution, data from experts on disease diagnosis for pregnant women is needed to be included as a knowledge base in the system. This study uses the approach or method of Certainty Factor (CF), namely by calculating according to the weight given by the expert and the answers given by the user. The aim is to help and provide a level of user confidence in diagnosing diseases with high accuracy. The results of the tests carried out by testing validation and accuracy between expert systems and those carried out by experts obtained a diagnosis with the same CFCombine value ..